Anaesthesia Management of Appendectomy Existed With Intracranial Arachnoid Cyst: A Case Report - Demirel, İsmail (Fırat University, 2012)
Arachnoid cysts may be intracranial or extracranial in the neuraxis and may present with headache and neurological signs or acutely with rupture and its complications. In this case a male patient who had a large intracranial arachnoid cyst in the left temporo-fronto-parietal region and operated by epidural anaesthesia for appendectomy was presented.

Araknoid kistler nöroaksiyel sistem içerisinde intrakranial veya ekstrakranial yerleşebilir, başağrısı benzeri nörolojik bulgular veya akut yırtılma gibi komplikasyonlar görülebilir. Sol temporo-fronto-parietal bölgede geniş intrakranial araknoid kisti olan ve apendektomi operasyonu için epidural anestezi uyguladığımız erkek hastayı sunduk.
Intrakranial Araknoid Kist Varlığında Appendektomi için Anestezi Yönetimi: Olgu Sunumu